Elementary and Intermediate Algebra: Concepts & Applications (6th Edition)

Published by Pearson
ISBN 10: 0-32184-874-8
ISBN 13: 978-0-32184-874-1

Chapter 7 - Functions and Graphs - 7.4 The Algebra of Functions - 7.4 Exercise Set: 19

Answer

$(g-f)(x)= x^2+2x-8$

Work Step by Step

RECALL: $(g-f)(x) = g(x) - f(x)$ Using the formula above gives: $(g-f)(x) = (x^2-5)-(-2x+3) \\(g-f)(x)= x^2-5-(-2x)-3 \\(g-f)(x)= x^2-5+2x-3 \\(g-f)(x)= x^2+2x-8$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.